Evaluation of Proximal Tubular Function with Tc-99-m Mercapto Acetyl Triglycine(MAG3)Clearance Determination in Patients with Renal Amyloidosis - Basoglu, T; Bakan, A; Albayrak, S; Sahin, M; Bernay, I; Cengiz, K (Soc Nuclear Medicine Inc, 1999)
…